Longitudinal changes in cerebral blood flow and their relation with cognitive decline in patients with dementia: Current knowledge and future directions - Weijs, Ralf W.J.; Shkredova, Daria A.; Brekelmans, Anna C.M.; Thijssen, Dick H.J.; Claassen, Jurgen A.H.R. (Alzheimer's & dementia, 2023)
The pathophysiology underlying cognitive decline is multifactorial, with increasing literature suggesting a role for cerebrovascular health. Cerebral blood flow (CBF) is an important element of cerebrovascular health, which raises questions regarding the relation between CBF and cognitive decline. Cross‐sectional studies demonstrate lower CBF in patients with cognitive decline compared to healthy age‐matched peers. Remarkably, longitudinal studies do not support a link between CBF reductions and cognitive decline. These studies, however, are often limited by small sample sizes and may therefore be underpowered to detect small effect sizes. Therefore, through a systematic review and meta‐analysis of longitudinal studies, we examined whether longitudinal changes in global CBF are related to cognitive decline in subjects with Alzheimer's disease, and qualitatively described findings on regional CBF. Considering the growing impact of dementia and the lack of treatment options, it is important to understand the role of CBF as a prognostic biomarker and/or treatment target in dementia.